Consumer Protection in Default in Buying and Selling On lineWith a Pre Order System (Case Study of Tas Nama Studios Products) - Ridwan, Muhammad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study aims to determine consumer protection against defaults in buying and selling online with a pre-order system and the legal responsibility of NAMA Studios bag business actors for their customers who do not receive the bags ordered. The research method used is a normative juridical research method that examines the basics of laws and regulations. The results of this research show that consumer protection for defaults in buying and selling online with a pre-order system has been accommodated in the Consumer Protection Act and includes defaults. Ways that consumers can do to protect their rights are through court and non-court methods. Consumers from the Studio Name business actor can sue the business actor for accountability based on Article 16 of the Consumer Protection Act.